Principles of dynamics - Hill, Rodney, 1921-2011 (Macmillan, 1964)
Principles of Dynamics presents classical dynamics primarily as an exemplar of scientific theory and method. This book is divided into three major parts concerned with gravitational theory of planetary systems; general principles of the foundations of mechanics; and general motion of a rigid body. Some of the specific topics covered are Keplerian Laws of Planetary Motion; gravitational potential and potential energy; and fields of axisymmetric bodies. The principles of work and energy, fictitious body-forces, and inertial mass are also looked into. Other specific topics examined are kinematics.